2019
DOI: 10.1111/1462-2920.14533
|View full text |Cite
|
Sign up to set email alerts
|

Endemic and cosmopolitan fungal taxa exhibit differential abundances in total and active communities of Antarctic soils

Abstract: SummaryOur understanding of the diversity and community dynamics of soil fungi has increased greatly through the use of DNA‐based identification. Community characterization of metabolically active communities via RNA sequencing has previously revealed differences between ‘active’ and ‘total’ fungal communities, which may be influenced by the persistence of DNA from nonactive components. However, it is not known how fungal traits influence their prevalence in these contrasting community profiles. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…This accentuates the fact that although the overall fungal alpha diversity (which is a qualitative measure) of total and active fungal communities does not differ significantly, the community composition (quantitative measure) is significantly different between the two communities. Such differences in total and active microbial community compositions were also reported from studies in forest soils [14,16,17], root-associated microbial communities [19], marine samples [46] and in the anaerobic digestion processes [43,47]. De Vrieze, et al [43] suggested that multiple microbial species are able to occupy the same niche with only a part of them being active at each time point.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This accentuates the fact that although the overall fungal alpha diversity (which is a qualitative measure) of total and active fungal communities does not differ significantly, the community composition (quantitative measure) is significantly different between the two communities. Such differences in total and active microbial community compositions were also reported from studies in forest soils [14,16,17], root-associated microbial communities [19], marine samples [46] and in the anaerobic digestion processes [43,47]. De Vrieze, et al [43] suggested that multiple microbial species are able to occupy the same niche with only a part of them being active at each time point.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, by extracting transcribed RNA and reverse transcriptase polymerase chain reaction (RT-PCR) based sequencing, the active members of fungal communities can be targeted [4,13,14]. This approach can even be used for targeting the universal DNA barcode region for fungi, the nuclear ribosomal internal transcribed spacer region (ITS) [15], and the few available studies showed that rRNA derived fungal communities differ from those derived from rDNA at the levels of richness, abundance of certain taxa and overall community composition [14,16,17,18,19]. However, such studies comparing total and active fungal communities have mostly been carried out either in surface soils from different biomes [14,16,17,20], or in communities associated with different plant species [19,21], but equivalent studies in subsurface aquatic ecosystems are largely missing.…”
Section: Introductionmentioning
confidence: 99%
“…In our data set, Chytrids were detected, particularly from samples from the AP, but had a low frequency despite often having a high relative abundance in samples where they were present. In Arctic systems Chytrids have been reported as the most abundant fungi group in ice cores (Hassett, Ducluzeau, & Collins, 2017; Hassett & Gradinger, 2016) and seawater (Comeau, Vincent, Bernier, & Lovejoy, 2016), A diversity of Chytrids and other basal fungi have been found in lakes on the Antarctic continent (Rojas‐Jimenez et al., 2017), and in Antarctica soils (Cox, Newsham, & Robinson, 2019) as well as on organic particles in the Scotia sea (Duret et al., 2020). Our study demonstrated the benefit of using a combination of marker genes for epiplastic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The fungi found throughout the Collins Glacier retreated soils are cosmopolitan. According to Cox et al [74], endemic and cosmopolitan fungi may have different dispersal strategies and degrees of adaptations to the extreme environment of these soils. Distribution patterns of microbes can influence their abundance in communities.…”
Section: Discussionmentioning
confidence: 99%